Senyawa Bioaktif Herpetofauna pada Penderita Diabetes Mellitus dan Hipertensi: Tinjauan Secara Patofisiologi - Aditya K. Karim; Rury Eprilurahman; Laksmindra Fitria; Paul J. Kawatu (Jurnal Biologi Papua, 2013)
Amphibians and reptiles (herpetofauna groups) produced of many compounds. The herpetofauna and their chemical compounds have been the subject of intense research interest for many years due to their potential in medical application and in lead compound development for new drugs. A number of different types of compounds have been identified from the glandular skin secretions of amphibians and venom or saliva of reptiles. These compounds have been shown to be active against gram-negative and gram-positive bacteria, fungi, enveloped viruses, diabetes mellitus, hypertension and cardiovascular disorder.Key words: Herpetofauna, diabetes mellitus, hypertension, drugs, pathophysiology